2006
DOI: 10.1148/rg.265055090
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Amyloid Angiopathy: CT and MR Imaging Findings

Abstract: Cerebral amyloid angiopathy (CAA) is an important but underrecognized cause of cerebrovascular disorders that predominantly affect elderly patients. CAA results from deposition of beta-amyloid protein in cortical, subcortical, and leptomeningeal vessels. This deposition is responsible for the wide spectrum of clinical symptoms and neuroimaging findings. Many cases of CAA are asymptomatic. However, when cases are symptomatic, patients can present with transient neurologic events, progressive cognitive decline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 25 publications
3
70
2
4
Order By: Relevance
“…[2][3][4]10,31 In the present study, there was no significant difference In a series of 2060 postmortem examinations, 19 of 59 (32%) cases of non-CAA-related intracerebral hemorrhage were found in the lobes, whereas 11 of 56 (20%) cases of CAA-related hemorrhage were located in the basal ganglia and brainstem. 32 A second postmortem study in hypertensive patients similarly demonstrated that CAA was associated with not only lobar but also deep brain hemorrhage.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…[2][3][4]10,31 In the present study, there was no significant difference In a series of 2060 postmortem examinations, 19 of 59 (32%) cases of non-CAA-related intracerebral hemorrhage were found in the lobes, whereas 11 of 56 (20%) cases of CAA-related hemorrhage were located in the basal ganglia and brainstem. 32 A second postmortem study in hypertensive patients similarly demonstrated that CAA was associated with not only lobar but also deep brain hemorrhage.…”
Section: Discussioncontrasting
confidence: 61%
“…The structural changes in the vascular wall related to CAA are associated with fibrinoid necrosis, focal vessel wall fragmentation and microaneurysms, which all predispose to blood vessel leakage. 31 These findings may suggest that pathological alterations associated with arterial stiffness, including an increase in pulsatile stimuli, may also underlay the association between MBs and CAA. Lee et al 11 demonstrated that left ventricular hypertrophy was an independent risk factor for the severity of MBs.…”
Section: Discussionmentioning
confidence: 93%
“…Intracerebral amyloid (also known as amyloid angiopathy) is not usually associated with systemic amyloidosis, and is characterized by protein deposition in the media and adventitia of small to medium sized cortical and leptomeningeal vessels, leading to vessel damage, hemorrhage, and infarction [5][6][7] . Chronic hypoperfusion leads to leukoencephalopathy and atrophy, manifesting as periventricular hypodensity on computed tomography (CT), or hyperintensity on T2-weighted images on magnetic resonance imaging (MRI) [6] .…”
Section: Brainmentioning
confidence: 99%
“…Chronic hypoperfusion leads to leukoencephalopathy and atrophy, manifesting as periventricular hypodensity on computed tomography (CT), or hyperintensity on T2-weighted images on magnetic resonance imaging (MRI) [6] . Recurrent subcortical and cortical hemorrhages sparing the deep white matter are typical, with susceptibility imaging raising diagnostic sensitivity by facilitating microhemorrhage detection [6,7] . At autopsy, amyloid deposition affects 33% of 6070 year olds, and 475% of individuals over 90 years [7] .…”
Section: Brainmentioning
confidence: 99%
See 1 more Smart Citation